United States Veto Power and Its Legal Implications for Palestinian Statehood - Shofiah Nur Hikmah; Sonny Saptoajie Wicaksono; Sergi Fernandez Alejandro (Faculty of Law, Universitas Sembilanbelas November Kolaka, 2025)
This study examines the use of the veto power by the United States within the United Nations Security Council and its impact on resolutions concerning the Israeli–Palestinian conflict. Since 1972, the United States has exercised its veto 86 times, including 49 instances in which resolutions critical of Israel or calling for ceasefires were blocked. Employing a normative legal research methodology, this paper analyzes both the regulatory framework governing veto use and its practical application in this context. The findings indicate that the United States’ use of the veto reflects its strategic political interests and has significant implications for the dynamics of the conflict. In particular, the repeated exercise of this power has contributed to diplomatic stagnation, heightened regional tensions, and diminished the effectiveness of the United Nations Security Council in addressing conflicts in the Middle East. Furthermore, the study highlights the long-term consequences of United States foreign policy for Palestinian self-determination and underscores the structural challenges faced by the international community in pursuing an equitable and sustainable resolution. This research contributes to ongoing debates on the role of great power influence within multilateral institutions and emphasizes the need for institutional reforms to promote greater fairness, accountability, and effectiveness in global governance.